Implementation of the Free Nutritious Meal Program to Help the Economy of the Community in Bintang Bayu District, Serdang Bedagai Regency - Khoirun Nisah Rangkuti; Salamuddin Salamuddin (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study aims to examine the implementation of the free nutritious food program, evaluate the economic situation of residents, and analyze improvements in social welfare in the Bintang Bayu District. The approach adopted was qualitative with a descriptive research design. Data collected through observation, interviews, and documentation studies were then processed through data reduction, data presentation, and conclusion drawing. Research indicates that initiatives to provide free nutritious food have a positive impact on reducing household expenses, improving access to adequate nutrition, and stimulating the local economy by engaging farmers and micro-entrepreneurs. Furthermore, these initiatives contribute to improving human resource capabilities, which in turn impacts the community's economic competitiveness. Therefore, it is crucial to strengthen collaboration, enhance human resource capabilities, and implement efficient monitoring mechanisms to optimize the sustainable success of these initiatives. Providing free nutritious food not only provides economic benefits but also makes a significant contribution to improving the social well-being of the community.